RANCANG BANGUN APLIKASI GAME MULTIPLAYER SEBAGAI ALAT BANTU PROSES PEMBELAJARAN BERBASIS WEBSOCKET - Mohammad Aryo Wibowo; I Made Arsa Suyadnya; Komang Oka Saputra (Jurnal SPEKTRUM, 2021)
The development of technology information is growing rapidly. For example in theeducation world, the purpose of interactive learning media is increasingly felt. With that purpose,an ICT-based learning process (Information Communication Technology) can be developedwhich has the concept of computer and multimedia learning. Computers can be used as asubstitute for books and also multimedia can be used as a substitute for teachers whenexplaining the material. In this study, to give an innovation in the learning models that usequizzes in the learning process, so it would be build a plan of a web socket based of multiplayergame application as a tool for learning process. To making this system, the advantage of websocket is to give a speed in exchanging information on the game system. Finally, the result ofthis application are to produce a web socket based of multiplayer game system design and howweb sockets work when used in a game. The results of the research produce a system designgame multiplayer based websocket. Based on BlackBox Testing and websocket testing. thebasic needs of the game are functionally fulfilled and the use of the system websocket providesa shorter lag time for requests and responses.